Molecular Docking of Gamma Amino Butyric Acid GABA on Rattus Norvegicus B-receptor as Antidiabetic - Meti Indrowati; Harlita; Umi Fatmawati; Joko Ariyanto; Estu Retnaningtyas (Postgraduate, University of Mataram, 2024)
Earlier research reported that GABA had a correlation with diabetes in processes of glucose homeostasis. This study aims to identify the validity of B-receptor Rattus norvegicus as GABA protein target, modeling the structure and knowing the binding affinity between GABA and B-receptor Rattus norvegicus through molecular docking. The research was carried out using in-silico method. The interaction of GABA with the target protein was determined using SuperPred, followed by modeling the protein target using SwissadMe. Ramachandran Plot and Errat Procheck are used to determine the validity of the protein target. Molecular docking was determined using Pyrx and PyMol. The results showed that GABA binding to the B- receptor Rattus norvegicus has biological activity as glucose oxidase inhibitor and antidiabetic. The conclusion are: B-receptor Rattus norvegicus is a valid protein target for binding to GABA; there are four 3-dimensional models of B-receptor Rattus norvegicus and the best model has 98.43% sequence identity; the binding affinity of GABA (ligand) on B-receptor Rattus norvegicus from the best model is -3.4 kcal/mol energy, 1.773 RMSD lower bound, and 1.81 RMSD upper bound. It is suggested that this research might be used as an empirical basis to further investigate GABA as antidiabetic.